Narrative as an alternative teaching approach of moral education - Saharuddin, Norzihani; Hussien, Suhailah; Yasin, Maizura (The Canadian Science Center and Education, 2021)
This paper discusses how the Narrative Approach has the potential to be one of the alternative teaching approaches in the teaching and learning process of Moral Education. This paper begins with an introduction to Moral Education in Malaysia. Also described in this paper is the history of how Moral Education in Malaysia began. Next, this paper discusses the Standard Curriculum and Assessment Document (DSKP) policy that drives the direction of the Education system in Malaysia in terms of, what is to be achieved and how it should be implemented in achieving the goals outlined. Then, the discussion continued by detailing the teacher training program for Moral Education teachers in Malaysia. Finally, this paper elaborates the description of the Narrative Approach and how its implementation in a teaching and learning process can provide the best added value to teachers and students; especially in producing „student-centered‟ learning.